The incidence of collagen-associated adverse events in pediatric population with the use of fluoroquinolones: a nationwide cohort study in Taiwan - Pei-Han Yu; Chih-Fen Hu; Jen-Wei Liu; Chi-Hsiang Chung; Yong-Chen Chen; Chien-An Sun; Wu-Chien Chien (BMC, 2020)
Abstract Background To evaluate the safety of using fluoroquinolones in pediatric population in Taiwan. Methods Patients aged 0~18 years old with fluoroquinolones prescriptions ≥5 consecutive days during year 2000 to 2013 were selected from the National Health Insurance Research Database, 4-time case number were selected as controls. We evaluated the patient's outcome after the use of fluoroquinolones by reviewing a newly diagnosis of the following collagen-associated adverse events by International Classification of Diseases, Ninth Revision, Clinical Modification codes, covering tendons rupture, retinal detachments, gastrointestinal tract perforation, aortic aneurysm or dissection. Results Of the enrolled patients (n = 167,105), collagen-associated adverse effects developed in 85 cases (0.051%) in 6-month tracking, including 0.051% in the fluoroquinolones study cohort (17 in 33,421) and 0.051% (68 in 133,684) in the fluoroquinolones free comparison cohort. The crude hazard ratio for collagen-associated adverse events in the fluoroquinolones group was 0.997 (0.586-1.696; p = 0.990). After adjusting for age, sex, catastrophic illness, low-income household, seasons, levels of urbanization, and healthcare, the corrected hazard ratio in 6-month tracking with FQs was 1.330 (95% CI; 0.778-2.276; p = 0.255). Conclusions There is no significant difference of collagen-associated adverse effects between fluoroquinolones group and fluoroquinolones free group from our data. We propose that fluoroquinolones for pediatric population in clinical practice may be not so harmful as previous references reported.